STRATEGI PENERJEMAHAN PADA LABEL PRODUK KECANTIKAN MEREK SENKA - Dessy Novia Azhari; Mangatur Sinaga; Nana Rahayu (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This study was describe the strategy used by translator in translating Senka’s label as beauty product. This study used descriptive qualitative research with theory of Vinay and Darbelnet. This study used eight senka’s product such as Senka Perfect Whip U, Senka Perfect Whip Acne Care, Senka Perfect Whip Collagen In, Senka Perfect White Clay, Senka All Clear Oil, Senka Perfect Aqua Rich-Extra Moist, Senka Aqua White Mask Extra White, Senka Perfect Aqua White Mask Soothing White. The technique of data analysis used is the first observing data from label product. The next is wrote word, phrases and sentences which related to translation strategy. Then select data based on word, phrases and sentences which appropriate to translation strategy. Last is deduced. The result from this study is 23 data found with 12 words, 3 phrases and 8 sentences in translation strategy. The strategy used was literal, transference, transposition and strategy with reduction.Key Word: beauty, label product, translation